Membongkar Mitosmenstruai Taboo (Kajian Tafsir Tematik Pendekatan Hermeneutik) - Mustaqim, Abdul (Musawa Jurnal Studi Gender dan Islam, 2007)
The concept of menstruation has both theological and mythological meanings, and is usually perceived with negativity. Such construction is partly caused by the transmission of Isra'iliyyat ideas in the Qur'anic exegesis books without any criticism. There[ore it is necessary for Muslims to deconstruct the misogynist mythologies of menstruation (haid), and then re-mrerprez it using the theological perspective as stated in Qur'anic verses dealing with the issues. By applying a thematic-hermeneutical method and historical approach to analyze the concept of menstruation in the Qur'an, this present study concludes that it has more humanistic view to menstruating women than those offered by the Jewish and Christian traditions. Al-Qur'an requires Muslims to be moderate in giving treatment to menstruating women. There are at least three main issues of menstruation addressed in the Qur'an. Firstly, issue concerning with the ways Muslims must treat their women when they menstruate. Secondly, problems related to 'iddah (women's time to wait before entering a new marriage after divorce), and the last is the idea of the obligation for menstruating women to wear jilbab.